Corporate agility: From functional to project-based organisations - Vasques, N.; Pereira, L. F.; Dias, Á. L.; Martinho, R. S.; Harfunche, A. (International Journal of Agile Systems and Management, 2024)
The number of project-based organisations (PBOs) is increasing, as is the number of organisations trying to make the transition from functional to PBOs. The lack of information about this transformation is a problem for the organisations trying to change. This research demonstrates the importance of information for organisations to be able to analyse and make a conscious decision to transition to a PBO. Twenty interviews were conducted with professionals from different companies, with different roles and working in different fields of action, to better understand the relevance of the problem. Through a qualitative analysis, it was possible to conclude that most organisations are affected in their project efficiency, depending on the field of action in which they work and on their staff. To solve this problem, organisations should work on their characteristics to potentiate the cooperation and collaboration between the different areas in the organisation.